Agroindustry as an Object and Representation of Power in the 20th Century - Alejandro Bocanegra (Histories of Postwar Architecture)
Agriculture, since its inception, has been intricately linked to symbolic and representative aspects of human existence. The knowledge and development of the agricultural process, achieved through advanced mastery of technique and control over nature, have historically been perceived as transcendental acts associated with connections to higher entities that explain and enable human existence. The intrinsic power embedded in this ideology has given rise to the conceptual subjugation definitions and property, whether individual or collective, as we currently understand them. This text aims to analyze the relationship between agriculture, architecture, and power within the context of the 19th-century industrial development and its influence on the political paradigm shift towards subsequent totalitarian regimes. To achieve this, it enumerates some of the typological hybridizations introduced to agricultural architectures as a consequence of the mechanization and industrialization processes production. Additionally, the text explores the styles, materiality, and character exhibited by these constructions, which played a pivotal role as instruments of political and economic control over 20th-century society. Simultaneously overseeing production, transportation, and consumption, these structures propagated an image of modernization and efficiency, disseminated as political propaganda. In conclusion, the text reflects upon the current obsolescence state and abandonment plaguing these buildings. Besides the inherent challenges of maintenance, their dilapidated condition is attributed in part to the negative connotations associated with them. These structures are perceived as problematic vestiges of the past, designed and erected under totalitarian regimes, and identified with oppression, lack of freedoms, and abuses of power.